Caritas in Veritate and Integral Human Development: A Critical Appraisal - Chathanatt, John (Asian Horizons, 2009)
At last it is out, some four years after it was first signaled. The long awaited third encyclical of Pope Benedict XVI, Caritas in Veritate (CV) is the first Social Encyclical of the Pope, issued on June 29, 2009, feast of SS Peter and Paul. Commemorating Pope Paul VI’s famous encyclical Populorum Progressio ( PP - On the Development of Peoples, 1967), CV focuses exclusively, as the sub-title of the encyclical puts it, on the integral development in today’s context of globalization. CV is addressed, as in the case of PP, to the Bishops, Priests and Deacons, Men and Women Religious, the Lay Faithful, and All People of Good Will, manifesting that the Pope wants it to be a document of universal significance.